Evaluación de tres protocolos de analgesia y anestesia en perros que ingresan a cirugía en el Hospital Docente Veterinario César Augusto Guerrero de la Universidad Nacional de Loja - Jirón Lituma, Yestin Alexander (2014)
This research was conducted at the Veterinary Teaching Hospital "César Augusto Guerrero" of the National University of Loja, within the area of Surgery (Operating Room); it lasted two months, 27 surgeries were performed, divided into 3 groups of 9 dogs each were of different age, weight, sex and race. The surgeries performed were three ovariohysterectomy (OVH), 3 laparotomies and 3 fractures in each group. The following variables were studied: decrease reflection loss and recovery, physiological constant before, during and after surgery, time of occurrence of surgical anesthesia, length of time of surgical anesthesia and analgesia also for signs before, during and after surgery. Atropine was used in doses of 0.044 mg / kg via Sc in the three protocols; In the first protocol Diazepam was used 0.2 to 0.5 mg / kg IV as tranquilizer and fentanyl dose of 0.005 to 0.2 mg / kg IV as an analgesic; Acepromazine the second protocol was used in a dose of 0.11 mg / kg Im as tranquilizer and Morphine Sulfate 0.6 mg / kg as an analgesic; Midazolam in the third protocol was used in doses of 0.1 to 0.3 mg / kg IV ketamine as tranquilizer and 5 mg / kg IV as an analgesic; inhalation anesthetic sevoflurane maintenance dose was 3.5%. The research patients who were operated with diazepam (0,2-0,5mg / kg iv) as a tranquilizer and fentanyl analgesic (0,005-0,2mg / kg iv) decreased reflexes faster than the other two protocols with an average of 3.2 minutes, with an average loss of 5.4 minutes and the recovery was 2.7 minutes. For the second variable of this research showed that heart rate in patients who were operated with the three protocols used not altered since it was within the normal range of 60-180 bpm, with a range of 108.2 to 138.5 bpm. The time of onset of surgical anesthesia protocol for one (Diazepam 0,2-0,5mg / kg iv) as a tranquilizer and fentanyl analgesic (0,005-0,2mg / kg iv) was 4.6 minutes, with the fastest of the three protocols; for the duration of one protocol anesthesia lasted longer with an average of 61.2 minutes. The duration of surgical anesthesia and analgesia were measured from the moment the patient loses reflexes until he begin to show sensory activity, regardless of time necessary to perform the procedure. The protocol three had the highest percentage of the presence of signs which were more noticeable the following urination, tachycardia, dyspnea, delirium, tic, vomiting, defecation, snoring before, during and after surgery.